Biocontrol and plant-growth-promoting capacities of actinobacterial strains from the Algerian Sahara and characterisation of Streptosporangium becharense SG1 as a promising biocontrol agent. Issue 9 (2nd September 2018) - Boukaya, Nassira; Goudjal, Yacine; Zamoum, Miyada; Chaabane Chaouch, Fawzia; Sabaou, Nasserdine; Mathieu, Florence; Zitouni, Abdelghani
ABSTRACT: Sixteen actinobacterial strains isolated from various ecological niches in the Algerian Sahara were screened for their biocontrol potential in root rot disease caused by Fusarium culmorum and their promotion of durum wheat growth. All actinobacteria were studied for in vitro antagonistic activity and plant-growth-promotion traits, for the production of cyanhydric acid, siderophores, chitinases and indole-3-acetic acid, and for the solubilisation of inorganic phosphate. Strongly antagonistic actinobacteria were selected for the biocontrol of F . culmorum in vivo and for the growth promotion of durum wheat plants in autoclaved and non-autoclaved soils. The Streptosporangium becharense strain SG1 exhibited remarkable positive results in all trials. Compared to untreated wheat seeds, the root rot severity index was decreased significantly ( P < 0.05) by all seed bacterization treatments. However, the highest protective effect was obtained by the strain SG1, which reduced the disease severity index from 77.8% to 16%, whereas it was only reduced to 24.2% by chemical seed treatment with Dividend®. Moreover, strain SG1 led to significant increases in the shoot length, root length and dry weight of plants, thus opening up interesting perspectives for possible exploration in crop enhancement.